Analysis of Multicultural Understanding in the Villages of Sindang Jaya, Sindang Jati, and Suro Bali - Hendra Harmi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to analyze the multicultural understanding in Sindang Jaya Village, Sindang Jati Village, and Suro Bali Village. Multicultural understanding is very important for instilling sympathy, respect, appreciation, and empathy towards adherents of different religions and cultures. The population taken in this study were all people who live in Sindang Jaya Village, Sindang Jati Village, and Suro Bali Village. The sampling technique used was purposive sampling with a total sample of 73 data, of which 23 people were from Sindang Jaya Village, 24 people were from Sindang Jati Village, and 26 people were from Suro Bali Village. The 73 respondents consisted of 33 Muslim respondents, 17 Buddhist respondents, 13 Hindus respondents, 9 Catholic respondents, and 1 Christian respondent. The data collection technique used was a non-test technique in the form of filling out a questionnaire. The instrument used in this study was a questionnaire sheet using a modified Likert scale with 4 answer choices. The results of the validity and reliability test indicated that the instrument used was valid and reliable. For the results of the analysis, the percentages for each respondent from the three villages are in the range of 76%-100% which enter the category of strongly agree based on the Likert scale interpretation table. This means that all respondents are categorized as strongly agree with the statements regarding the multicultural indicators proposed in the questionnaire. This shows that the people who live in Sindang Jaya Village, Sindang Jati Village, and Suro Bali Village have a high level of multicultural understanding